Trace-elemental data (Mn/Ca) of benthic foraminifers from core-top sediments of Gullmarsfjorden, Sweden's west coast - Brinkmann, Inda (Lund University, 2023)
Dataset of Mn/Ca in Bulimina marginata and Nonionellina labradorica (CTG-labelled) acquired by Laser-Ablation Inductively Coupled Mass Spectrometry (LA-ICP-MS). Comprises data of the three most-recently formed chambers (n, n-1 and n-2), as well as the proloculus area (p; B. marginata only). The specimens were collected from core-top samples of two sites in the fjord Gullmarn on the west coast of Sweden over a temporal gradient spanning the years 2018 and 2019. The data set is part of a study exploring the response of foraminiferal Mn/Ca to low-oxygen bottom-water conditions.

Sediment from the fjord Gullmarn was sampled in September 2018, February 2019 and June 2019 (R/V Oscar von Sydow and R/V Skagerak, respectively) at two sites: GF 117 (115–117 m water depth; 58º19.695’N, 11º33.147’E) and GF 71 (69–71 m water depth; 58º17.116’N, 11º30.546’E). Sediment cores were recovered with a GEMAX® twin-barrel corer (modified Gemini corer, 9 cm diameter, from Oy Kart AB, Finland). The top 0-1 and 1-2 cm of the cores were collected and CTG-labelled to identify living foraminifera. Bulimina marginata and Nonionellina labradorica specimens were selected and bleached (NaOCl 5%). Trace element concentrations of test walls were analysed using a Bruker Aurora Elite (quadrupole) ICP‐MS and a 193 nm Cetac Analyte G2 excimer laser installed with a two volume HelEx2 sample cell (Dept. of Geology, Lund University, Lund, Sweden). U.S. National Institute of Standards and Technology SRM NIST610 was used as external calibration material with GeoReM (Geological and Environmental Reference Materials; Jochum et al., 2005) composition values (via http://georem.mpch-mainz.gwdg.de). Please contact the main author for further details.

Dataset över Mn/Ca i skal av Bulimina marginata och Nonionellina labradorica (CTG-märkta) analyserades genom laserspektroskopi (LA-ICP-MS). Mn/Ca mättes i de tre senast bildade kamrarna (n, n-1, n-2), och i skal av Bulimina marginata analyserades även de första kamrarna, så kallade 'proloculus' (p). Exemplaren provtogs från ytsediment från två platser i Gullmarsfjorden under 2018 och 2019. Datasetet är en del av en studie som undersöker hur Mn/Ca kvoten i foraminiferers skal påverkas av förändrad syrehalt i bottenvatten.

Sediment från Gullmarsfjorden provtogs i september 2018, februari 2019 och juni 2019 (R/V Oscar von Sydow respektive R/V Skagerak) på två platser: GF 117 (115–117 m vattendjup; 58º19.695’N, 11º33.147’E) och GF 71 (69–71 m vattendjup; 58º17.116’N, 11º30.546’E). Proven togs med en GEMAX® twin-barrel corer (modifierad Gemini corer, 9 cm diameter, från Oy Kart AB, Finland). Sedimentprov togs från ytan av sedimentkärnorna (0-1 cm och 1-2 cm) och CTG tillsattes för att särskilja mellan levande och döda foraminiferer. Utvalda (nu döda) exemplar blektes (NaOCl 5%) innan analyserna. Koncentrationerna av spårelementinnehållet i skalväggen analyserades med laserspektroskopi (LA-ICP-MS; geologiska institutionen, Lunds universitet, Lund, Sverige). För ytterligare information, se den engelska katalogposten.
Spårämnesdata (Mn/Ca) från bottenlevande foraminiferer, provtagna i ytsediment från Gullmarsfjorden, Sverige
Keywords: TRACE ELEMENTS; FJORDS; benthic foraminifera; manganese; deoxygenation; hypoxia; Climate Science; Klimatvetenskap; Environmental Sciences; Miljövetenskap; Geochemistry; Geokemi; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser